Energy Sub-Metering Data Acquisition System - Bulbenkiene, V.; Pecko, A.; Zulkas, E.; Kuprinavicius, A.; Sokolov, A.; Mumgaudis, G. (Elektronika ir Elektrotechnika, 2011)
This paper describes the creation of a system that acquires building energy sub-metering data. The system is designed in a way that allows it to use different sensors for different energy resources sub-metering. A wireless communication standard that allows to achieve the best combination of communication range, low power sub-metering and to give the system more flexibility is chosen. This paper shows how electrical energy sub-metering data is extracted by the sensor node from the current wire without any physical invasion and wirelessly passed to the concentrator. Non-standard error processing solutions and their application to the prototype, and issue-specific solutions related to energy transmission and processing using standard wired and wireless transmission protocols are analyzed. Ill. 4, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.366